An Analysis of Meaning in Adele’s Songs in The Album 21 - Salim, Nadia; Taufiqrianto Dako, Rahman; Danial, Haris (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This research aims to identify the types of meaning found in the lyrics of Adele’s song from the album 21, based on the theory proposed by Geoffrey Leech. Employing a qualitative method, the study analyzed selected song lyric to uncover various types of meaning conveyed through Adale’s expressive and poetic language. The analysis focuses on Leech’s seven types of meaning: conceptual, connotative, social, affective, reflected, collocative, and thematic. The data were taken from six song in the album, with a total of 17 data points analyzed. The results show that conceptual meaning is the most frequently found, appearing in 7 data points, while collocative meaning appears the least, with only 2 data found. This indicated that context plays an important role in hos song lyrics are interpreted. Through this study, it is expected that readers can gain insight into how meaning in song lyrics can be analyzed from a linguistic, particularly semantic perspective.